Genetic influences on human epilepsy - Buono, Russell J. (Henry Stewart Talks, 2011)
Genetic techniques used to identify epilepsy genes, Seizures in mice, Translating mice genes to human genes, Identified epileptic genes, Neural transmission genes, Ion flux genes, Neuro-development genes
Updated at 2021/05/30